PSYCHOLOGICAL CHARACTERISTICS OF THE DEVELOPMENT OF CRITICAL THINKING IN ADOLESCENTS - Turgunov Abdumannop Inomjonovich (Frontline Social Sciences and History Journal, 2024)
This article reveals the psychological features of developing critical thinking in teenagers. Also, this article describes in detail the influence of social and psychological qualities of critical thinking in teenagers and its connection with various situations.